Effect of intermolecular interaction on ionic conductivity of CMC-DTAB plasticized with Ec based solid biopolymer electrolyte - Nurhasniza, Mamajan Khan; Noor Saadiah, Mohd Ali; Ahmad Salihin, Samsudin (Trans Tech Publications, 2021)
The present work highlights on the structural and conduction properties of the solid biopolymer electrolytes (SBPE) based carboxymethyl cellulose (CMC) doped dodecyltrimethyl ammonium bromide (DTAB) and plasticized with ethylene carbonate (EC). The SBPE exhibits high ionic conductivity at room temperature where the highest value reaching 1.0 × 10-3 S cm-1 for sample containing with 10 wt. % of EC and increases the ionic conductivity when temperature was increased. Complexation within the SBPE has been confirmed by the FTIR analysis where the intermolecular interaction has improvised the coordination between CMC-DTAB and EC resulting in better structural and conductivity ability. The findings suggest that the great potential of CMC and make it promising to serve as an electrolyte for electrochemical devices.